2018
DOI: 10.1186/s13099-018-0278-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of multiplex PCR and multi-color fluorescent in situ hybridization (m-FISH) coupled protocol for detection and imaging of multi-pathogens involved in inflammatory bowel disease

Abstract: BackgroundSeveral pathogens have been debated to play a role in inflammatory bowel disease (IBD) including Crohn’s disease (CD). None of these pathogens have been investigated together in same clinical samples. We developed a multiplex PCR and multi-color fluorescent in situ hybridization (m-FISH) protocols for simultaneous detection of CD-associated pathogens including Mycobacterium avium subspecies paratuberculosis (MAP), Klebsiella pneumoniae, and adherent-invasive Escherichia coli strain LF82.MethodsThe mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…As FISH is not a routine diagnostic tool, the frequency of this is unknown. FISH should be considered more frequently as part of routine diagnostics like in human IBD (43)(44)(45), particularly in severe or difficult to control cases. Results may identify different underlying phenotypes of CIE, that more closely resemble human CD.…”
Section: Discussionmentioning
confidence: 99%
“…As FISH is not a routine diagnostic tool, the frequency of this is unknown. FISH should be considered more frequently as part of routine diagnostics like in human IBD (43)(44)(45), particularly in severe or difficult to control cases. Results may identify different underlying phenotypes of CIE, that more closely resemble human CD.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies have reported lower incidence of MAP infection among CD patients in comparison to healthy controls, which might be due to the fact that different methodology was used for MAP detection in human samples [15]. Detection of MAP in cultures of blood, breast milk, and intestinal tissue was reported using RT-PCR and nested PCR techniques [16]. At least one third of CD patients may not have MAP infection or they may have it at levels below the limit of detection provided by available techniques.…”
Section: Introductionmentioning
confidence: 94%
“…After 24 h of infection with MAP, monocyte-derived macrophages were washed twice with PBS to remove extracellular bacteria, and then antibiotics were added, and the cells were incubated for an additional 24 h. Monocyte-derived macrophages were collected at three time points: 24, 48, and 72 h. The cells were lysed, and then the samples were centrifuged at 14,000 rpm for 20 min. Supernatants were collected and the LIVE/DEAD™ BacLight™ Bacterial Viability Kit (Thermo Fisher Scientific, Waltham, MA, USA) was used according to the manufacturer's protocol as described earlier [16]. Briefly, 100 µL of each bacterial suspension was pipetted into separate wells of a 96-well flat-bottom microplate in triplicate and mixed with 100 µL of stain solution.…”
Section: Measurement Of Map Viability In Infected Macrophagesmentioning
confidence: 99%
“…One of the most debated explanations for the contradictory effect of nicotine is the association of CD with microbial infection, which lacks in UC. Among the most discussed pathogens associated with CD is MAP [7,8,[49][50][51][52][53][54][55][56][57][58].…”
Section: Differences In Immunological Response Profile Between Crohn'mentioning
confidence: 99%